Tratamento de materiais contaminados com bifenilas policloradas (PCBS) via extração convencional e fluído supercrítico - Silva, Dannielle Janainne da (2008)
The decontamination of the materials has been subject of some studies. One of the factors that it increases the pollution is the lack of responsibility in the discarding of toxic trash, as for example the presence of PCB (Polychlorinated Biphenyls) in the environment. In the Brazilian regulations, the material contaminated with PCB in concentrations higher than 50 ppm must be stored in special places or destroyed, usually by incineration in plasma furnace with dual steps. Due to high cost of the procedure, new methodologies of PCBs removal has been studied. The objective of this study was to develop an experimental methodology and analytical methodology for quantification of removal of PCBs through out the processes of extractions using supercritical fluid and Soxhlet method, also technical efficiency of the two processes of extraction, in the treatment of contaminated materials with PCBs. The materials studied were soils and wood, both were simulated contamination with concentration of 6.000, 33.000 and 60.000 mg of PCB/ kg of materials. Soxhlet extractions were performed using 100 ml of hexane, and temperature of 180 ºC. Extractions by fluid supercritical were performed at conditions of 200 bar, 70°C, and supercritical CO2 flow-rate of 3 g/min for 1-3 hours. The extracts obtained were quantified using Gas chromatography-mass spectrometry (GC/MS). The conventional extractions were made according to factorial experimental planning technique 22, with aim of study the influence of two variables of process extraction for the Soxhlet method: contaminant concentration and extraction time for obtain a maximum removal of PCB in the materials. The extractions for Soxhlet method were efficient for extraction of PCBs in soil and wood in both solvent studied (hexane and ethanol). In the experimental extraction in soils, the better efficient of removal of PCBs using ethanol as solvent was 81.3% than 95% for the extraction using hexane as solvent, for equal time of extraction. The results of the extraction with wood showed statistically it that there is not difference between the extractions in both solvent studied. The supercritical fluid extraction in the conditions studied showed better efficiency in the extraction of PCBs in the wood matrix than in soil, for two hours extractions the obtain percentual of 43.9 ± 0.5 % for the total of PCBs extracted in the soils against 95.1 ± 0,5% for the total of PCBs extracted in the wood. The results demonstrated that the extractions were satisfactory for both technical studied